2016
DOI: 10.1128/jvi.02820-15
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Binding of HIV-1 Matrix Protein: Dependence on Bilayer Composition and Protein Lipidation

Abstract: By assembling in a protein lattice on the host's plasma membrane, the retroviral Gag polyprotein triggers formation of the viral protein/membrane shell. The MA domain of Gag employs multiple signals-electrostatic, hydrophobic, and lipid-specific-to bring the protein to the plasma membrane, thereby complementing protein-protein interactions, located in full-length Gag, in lattice formation. We report the interaction of myristoylated and unmyristoylated HIV-1 Gag MA domains with bilayers composed of purified lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 81 publications
5
43
0
Order By: Relevance
“…However, it is known that cholesterol is crucial for virus infectivity3637 and that Gag can sense cholesterol3839. It was recently described that PIP 2 could form clusters in the presence of cholesterol alone40.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is known that cholesterol is crucial for virus infectivity3637 and that Gag can sense cholesterol3839. It was recently described that PIP 2 could form clusters in the presence of cholesterol alone40.…”
Section: Discussionmentioning
confidence: 99%
“…Self-assembled monolayers (SAMs) of HC18 tethers were formed on 3” diameter silicon wafers as previously described [32]. Sparsely-tethered bilayer lipid membranes (stBLMs) were formed by exposing the SAM to the vesicle suspension for 60 minutes in a NIST reflectivity flow cell, followed by a rinse with 40 ml deionized water [28]. …”
Section: Methodsmentioning
confidence: 99%
“…A recent SPR study examined the role of lipids in membrane binding of the myristoylated and non-myristoylated forms of MA [28] and reported that myristoylation increases MA affinity to PC/PS membranes by factors up to ~20 depending on membrane charge. Cholesterol in PC/PS membranes increased MA affinity only mildly, while it increased it much more in PIP 2 -containing PC/PS membranes, in particular for the myristoylated protein.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… Note Added in Proof After this paper was submitted and reviewed, a preprint appeared on-line describing studies of MA binding to synthetic solid-supported bilayers by surface plasmon resonance spectroscopy [113]. …”
mentioning
confidence: 99%